How platinum oxide affects the degradation analysis of PEM fuel cell cathodes. (14th April 2021) - Bernhard, David; Kadyk, Thomas; Krewer, Ulrike; Kirsch, Sebastian
Abstract: In this work, proton exchange membrane fuel cell cathodes are degraded with accelerated-stress-tests.These PtCo containing cathodes are analyzed at begin-of-life and end-of-test with a dedicated diagnostic procedure. For every individual load point, the oxygen transport resistance and voltage losses due to the formation of platinum oxides were obtained in addition to commonly measured electrochemical surface area, high frequency resistance, as well as cathode ionomer resistance. These data were used to break down the voltage losses into six different contributors. With this break down, performance gains and performance losses were determined at end-of-test. At low current densities, it was found that voltage losses due to degradation are dominated by the loss of specific activity and catalyst surface area - in line with the state-of-the-art knowledge. But by quantifying the losses from platinum oxide formation explicitly, we show that end-of-test an unassigned voltage loss is not only present at highest current densities, but already at low current density. More precisely, the unassigned voltage loss shows a linear increase with decreasing half cell voltage and is independent from the chosen accelerated stress test. As this unassigned loss depends on half cell voltage, it might arise from ionomer adsorption. Highlights: New diagnostic routine to determine platinum oxide related voltage losses explicitly Oxide related voltages losses depend only on half potential voltage. Voltage loss break down of end-of-test voltage losses into 6 different contributors. Unassigned voltage loss is severely underestimated if oxide formation is neglected